FASHION AND BEAUTY PERSPEKTIF HUKUM ISLAM - Aliasyadi Aliasyadi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Fashion and beauty is part of human nature. Islam called it as fitrah.But Islam sets the rules in the form of conditions that must beconsidered so that fashion and beauty does not become somethingcontrary to Islamic law. This paper will answer 3 issues: how thehistory of beauty in human life, how the Islamic view of thedevelopment of fashion and beauty, and what are the conditionsspecified in Islam. This paper is a library research using a normativedescriptive approach by examining the opinions of ulama and modernphenomena in human society.